2018
DOI: 10.1167/iovs.17-23453
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Structural and Functional Abnormalities in Female Carriers of Pathogenic Variants in theRPGRGene

Abstract: PURPOSE. The purpose of this study was to investigate the phenotype and long-term clinical course of female carriers of RPGR mutations.METHODS. This was a retrospective cohort study of 125 heterozygous RPGR mutation carriers from 49 families.RESULTS. Eighty-three heterozygotes were from retinitis pigmentosa (RP) pedigrees, 37 were from cone-/cone-rod dystrophy (COD/CORD) pedigrees, and 5 heterozygotes were from pedigrees with mixed RP/CORD or unknown diagnosis. Mutations were located in exon 1-14 and in ORF15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
4
46
1
Order By: Relevance
“…We and others have previously found that the PR + RPE complex has been suggested to be a good predictor of the visual acuity. 15,[28][29][30] Similar results were found in this study because the PR + RPE complex correlated strongly with the BCVA, and it was the only parameter that remained significant after correction for multiple testing. The PR + RPE complex can potentially be used to identify early structural changes before the visual acuity loss may be noticeable, which can be particularly useful in diseases with relatively slow disease progression such as RHO-associated RP.…”
Section: Discussionsupporting
confidence: 87%
“…We and others have previously found that the PR + RPE complex has been suggested to be a good predictor of the visual acuity. 15,[28][29][30] Similar results were found in this study because the PR + RPE complex correlated strongly with the BCVA, and it was the only parameter that remained significant after correction for multiple testing. The PR + RPE complex can potentially be used to identify early structural changes before the visual acuity loss may be noticeable, which can be particularly useful in diseases with relatively slow disease progression such as RHO-associated RP.…”
Section: Discussionsupporting
confidence: 87%
“…It is believed that frameshift mutations in the exons that encode the N-terminal RCC1-like domain of RPGR are more prone to nonsense-mediated decay (NMD), leading to lower levels of the transcript and may therefore be more likely to cause severe RP phenotypes [4]. Furthermore, the N-terminal RCC1-like domain of RPGR is shared between RPGR ORF15 and RPGR [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] isoforms. Since RPGR [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is also expressed in primary cilia, it is believed that mutations in the N-terminal RCC1-like domain may lead to retinal degeneration with ciliary abnormalities, as shown in previous studies [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood samples according to standard protocols. Genetic analysis was performed at the Department of Clinical Genetics of the Amsterdam University Medical Centers (Amsterdam UMC, The Netherlands), the Netherlands, and methods used have been published previously [2,10,47]. The primers used in this study can be accessed upon reasonable request.…”
Section: Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations